Comparing Personality Traits and Resilience Among Treatment-Seeking and Treatment-avoidant Elderly with Health Anxiety Disorde - Masood Ghorbanalipour; Somayeh Hajihatamlou; Bahare Hosseinlou; Ameneh Zardi Nahr (Elderly Health Journal)
Introduction: Treatment-seeking behaviors in elderly patients can facilitate timely diagnosis and effective intervention for health issues, whereas treatment-avoidant behaviors may contribute to the progression of diseases and an increased burden of chronic conditions. Understanding the psychological factors influencing these behaviors is crucial for improving health outcomes in this population. This study aimed to compare personality traits and resilience among elderly patients with health anxiety who exhibit treatment-seeking versus treatment-avoidant behaviors. Methods: This fundamental research employed a causal-comparative design. The statistical population consisted of elderly patients with health anxiety who referred to Healthcare Centers in West Azerbaijan Province, Iran, in 2023. A sample of 60 patients was selected through convenience sampling. Data were collected using the NEO Five-Factor Inventory, the Connor-Davidson Resilience Scale, and the Salkowski Health Anxiety Inventory. Hypotheses were tested using MANOVA. Results: Significant differences were observed between treatment-seeking and treatment-avoidant patients in terms of personality traits and resilience (F (2, 57) = 11.28, p < 0.05). The findings highlighted that individuals with certain personality traits and higher levels of resilience were more inclined to seek treatment. Conclusion: The study underscores the importance of considering personality traits and resilience as key factors when developing strategies for encouraging appropriate healthcare-seeking behaviors among elderly patients with health anxiety. Understanding these factors can inform tailored interventions to reduce treatment avoidance and improve overall health management.